Contemporary management of chronic rhinosinusitis with nasal polyposis in aspirin‐exacerbated respiratory disease: an evidence‐based review with recommendations. Issue 12 (2nd August 2016) - Levy, Joshua M.; Rudmik, Luke; Peters, Anju T.; Wise, Sarah K.; Rotenberg, Brian W.; Smith, Timothy L.
Abstract : Background: Chronic rhinosinusitis (CRS) in aspirin‐exacerbated respiratory disease (AERD) represents a recalcitrant form of sinonasal inflammation for which a multidisciplinary consensus on patient management has not been reached. Several medical interventions have been investigated, but a formal comprehensive evaluation of the evidence has never been performed. The purpose of this article is to provide an evidence‐based approach for the multidisciplinary management of CRS in AERD. Methods: A systematic review of the literature was performed and the guidelines for development of an evidence‐based review with recommendations were followed. Study inclusion criteria included: adult population >18 years old; CRS based on published diagnostic criteria, and a presumptive diagnosis of AERD. We focused on reporting higher‐quality studies (level 2 or higher) when available, but reported lower‐quality studies if the topic contained insufficient evidence. Treatment recommendations were based on American Academy of Otolaryngology (AAO) guidelines, with defined grades of evidence and evaluation of research quality and risk/benefits associated with each treatment. Results: This review identified and evaluated the literature on 3 treatment strategies for CRS in AERD: dietary salicylate avoidance, leukotriene modification, and desensitization with daily aspirin therapy. Conclusion: Based on the available evidence, dietary salicylate avoidance and leukotriene‐modifying drugs are options following appropriate treatment with nasal corticosteroids and saline irrigation. Desensitization with daily aspirin therapy is recommended following revision endoscopic sinus surgery (ESS).